Net Neutrality and 5G in India: A Policy Delphi Survey - Mitra, Anuradha; Sridhar, V.; K. Sarangi, Gopal (Revista de Direito, Estado e Telecomunicacoes, 2024)
[Purpose] The debate over Net Neutrality (NN) that dominated discussion in the domain of Internet and telecommunications for over two decades, has largely been settled in favour of the principle of an open, non-discriminatory regime for all traffic travelling over networks. The rapid commercialisation of 5G mobile telecom technologies in telecom markets, however, draws regulatory attention once again, to aspects of NN regimes in apparent conflict with the requirements of the new technology. The emerging discussion has prompted reviews of NN policies in many countries. [Methodology] This paper uses a policy Delphi to assess expert and stakeholder opinion on the likely impact of 5G of the NN regime in India and what, if any, modifications and alterations are required to enable proliferation of 5G services in the country. [Findings] The paper arrives at a set of policy recommendations for management of the NN regime in India in the context of 5G technology, markets and services. [Practical Implications and Value] These recommendations would be of practical utility to regulators and administrators in other countries as 5G is adopted in their telecommunications sectors. [Purpose] The debate over Net Neutrality (NN) that dominated discussion in the domain of Internet and telecommunications for over two decades, has largely been settled in favour of the principle of an open, non-discriminatory regime for all traffic travelling over networks. The rapid commercialisation of 5G mobile telecom technologies in telecom markets, however, draws regulatory attention once again, to aspects of NN regimes in apparent conflict with the requirements of the new technology. The emerging discussion has prompted reviews of NN policies in many countries. [Methodology] This paper uses a policy Delphi to assess expert and stakeholder opinion on the likely impact of 5G of the NN regime in India and what, if any, modifications and alterations are required to enable proliferation of 5G services in the country. [Findings] The paper arrives at a set of policy recommendations for management of the NN regime in India in the context of 5G technology, markets and services. [Practical Implications and Value] These recommendations would be of practical utility to regulators and administrators in other countries as 5G is adopted in their telecommunications sectors. [Purpose] The debate over Net Neutrality (NN) that dominated discussion in the domain of Internet and telecommunications for over two decades, has largely been settled in favour of the principle of an open, non-discriminatory regime for all traffic travelling over networks. The rapid commercialisation of 5G mobile telecom technologies in telecom markets, however, draws regulatory attention once again, to aspects of NN regimes in apparent conflict with the requirements of the new technology. The emerging discussion has prompted reviews of NN policies in many countries. [Methodology] This paper uses a policy Delphi to assess expert and stakeholder opinion on the likely impact of 5G of the NN regime in India and what, if any, modifications and alterations are required to enable proliferation of 5G services in the country. [Findings] The paper arrives at a set of policy recommendations for management of the NN regime in India in the context of 5G technology, markets and services. [Practical Implications and Value] These recommendations would be of practical utility to regulators and administrators in other countries as 5G is adopted in their telecommunications sectors. [Purpose] The debate over Net Neutrality (NN) that dominated discussion in the domain of Internet and telecommunications for over two decades, has largely been settled in favour of the principle of an open, non-discriminatory regime for all traffic travelling over networks. The rapid commercialisation of 5G mobile telecom technologies in telecom markets, however, draws regulatory attention once again, to aspects of NN regimes in apparent conflict with the requirements of the new technology. The emerging discussion has prompted reviews of NN policies in many countries. [Methodology] This paper uses a policy Delphi to assess expert and stakeholder opinion on the likely impact of 5G of the NN regime in India and what, if any, modifications and alterations are required to enable proliferation of 5G services in the country. [Findings] The paper arrives at a set of policy recommendations for management of the NN regime in India in the context of 5G technology, markets and services. [Practical Implications and Value] These recommendations would be of practical utility to regulators and administrators in other countries as 5G is adopted in their telecommunications sectors.